ANALISIS POTENSI FINANCIAL DISTRESS DENGAN MENGGUNAKAN ALTMAN Z SCORE PADA PERUSAHAN PENERBANGAN (DAMPAK PANDEMI COVID-19 DENGAN PENUTUPAN OBJEK WISATA DAN PSBB) - Affandi, Muhammad Rizal; Meutia, Rita (J-MIND (Jurnal Manajemen Indonesia), 2021)
This study aims to identify and analyze the potential for financial distress in airlines at Indonesia. The object of this research is the airlines listed on the Indonesia Stock Exchange (BEI), namely PT. Garuda Indonesia Tbk and PT. AirAsia Indonesia Tbk. The data used is in the form of financial reports that have been published on the Indonesia Stock Exchange through the website (www.idx.co.id) in the first quarter of 2020 – third quarter of 2020. The data analysis technique uses the Altman Z Score in predicting potential financial distress. The results of the study found that PT Garuda Indonesia Tbk and PT AirAsia Indonesia Tbk were in financial distress or in an unhealthy financial condition, and were classified as companies that have the potential to experience bankruptcy. Research shows that PT AirAsia Indonesia Tbk has a higher potential for bankruptcy than PT Garuda Indonesia Tbk.